Clinical characteristics and health care received among patients with type 2 diabetes attending secondary and tertiary healthcare facilities in Mwanza Region, Tanzania: a cross-sectional study - Mariam J. Munyogwa; Reuben William; Stephen M. Kibusi; Nyasiro S. Gibore (BMC, 2020)
Abstract Background Tanzania is among the sub-Saharan African countries facing a tremendous increase in the burden of type 2 diabetes mellitus. In order to provide diabetes health care services, the government has established diabetes care clinics in secondary and tertiary healthcare facilities. However, previous studies have demonstrated a disparity in availability of supplies and equipment for provision of diabetes health care services at these healthcare facilities. This study aims to assess the clinical characteristics and health care received among patients with type 2 diabetes attending secondary and tertiary healthcare facilities in Mwanza Region, Tanzania. Methods A cross-sectional study was conducted in Mwanza Region from June to September, 2018.Three hundred and thirty patients were selected by systematic random sampling from three healthcare facilities. A structured questionnaire was utilized to collect information on patient characteristics, health care received and patient perception of care. Patient blood pressure, blood glucose, weight and height were measured during the study. Percentages, chi-square tests and multivariable analysis were conducted to obtain the proportions, make comparisons and determining the correlates of tertiary-level healthcare facility. Results Approximately half of respondents (54.5%) were from secondary healthcare facilities. The prevalence of hypertension (63.3%), hyperglycemia (95.8%) and obesity (93.3%) were high. The prevalence of hyperglycemia was slightly higher at secondary-level healthcare facility (p = 0.005). The proportion of respondents recently diagnosed with diabetes (≤ 10 years) was significantly higher at tertiary-level healthcare facility (p = 0.000). The prevalence of diabetes related complications was higher at tertiary-level healthcare facility (80.7% versus 53.3%, p = 0.000). Assessments of body weight, blood pressure, blood glucose, feet and eye examination were conducted on a monthly basis at all facilities. None of the respondents had undergone lipid profile testing. All of the respondents (100%) received care from a nurse during diabetes clinic visits and half of the respondents (49.7%) also received care from a clinician. Relatively young patients, married and recently diagnosed patients were more likely to attend clinic at tertiary facilities. Tertiary-level healthcare facilities were more likely to have patients with complications and to have a dietitian available at the clinic.